DINAMIKA SOSIAL EKONOMI MASYARAKAT YANG TINGGAL DI SEKITAR KAWASAN PERTAMBANGAN - Dian Putri; Raemon Raemon; Laxmi Laxmi (KABANTI : Jurnal Kerabat Antropologi, 2022)
This study uses Kingsley Davis Social Dynamics theory to solve problems in the field with the Ethnographic Method, data collection using observation techniques and in-depth interviews and purposive sampling informant selection techniques. Data were analyzed descriptively. This Nickel mining activity by PT NPM took experts on agricultural land belonging to the people of Matarape Village without the consent of the local community, the acquisition of agricultural land that reached 300 hectares made the farmers in Matarape Village suffer huge losses, not only losses, their economy also became paralyzed. In total, this is because the farmers can no longer produce cashew nuts as their source of income. The damage to agricultural land carried out by PT NMP triggered a conflict between the community and the PT NPM company, where the majority of people who work as farmers demanded compensation for the destruction and use of agricultural land which reached up to 300 hectares was used for road construction and mining activities of PT. This NPM also resulted in changes in the livelihoods of the people of Matarape Village